Estimation of Domestic Waste Volume as A Sustainable Waste Management Efforts In Mataram City - Uzlifatul Azmiyati; Gendewa Tunas Rancak (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
In this research, the problem formulation is based on the central issues in sustainable domestic waste management. In domestic waste management, information is needed regarding the existing volume and the projected volume of domestic waste in the next ten years. This study's objectives are (1) to determine the volume of domestic waste in Mataram, (2) to project the volume of domestic waste in the next ten years in the city of Mataram. Based on the data analysis results, it is found that the generation of domestic waste in Mataram City in units of weight is 0.4 kg/person/day, while the amount of domestic waste generation in Mataram City in volume units is 0.0020 m3/day. The composition of domestic waste in Mataram City is dominated by wet organic waste at 64%, followed by dry organic waste, non-medical hazardous waste, and plastic packaging, which have the same percentage, namely 6%. The type of waste with the least amount is metal and hazardous medical waste, only 1%. The projected population growth for the City of Mataram has increased with an average growth per year of 1.99%. An increase followed this in the projected waste generation. In 2020 the population is 496,401 people with a waste generation of 1,005 m3/year. Meanwhile, in 2029 the total population of 583,571 people will generate 1,182 m3/year of waste.